A study of content authentication in proxy-enabled multimedia delivery systems: Model, techniques, and applications - DENG, Robert H. (Institutional Knowledge at Singapore Management University, 2009)
Compared with the direct server-user approach, the server-proxy-user architecture for multimedia delivery promises significantly improved system scalability. The introduction of the intermediary transcoding proxies between content servers and end users in this architecture, however, brings unprecedented challenges to content security. In this article, we present a systematic study on the end-to-end content authentication problem in the server-proxy-user context, where intermediary proxies transcode multimedia content dynamically. We present a formal model for the authentication problem, propose a concrete construction for authenticating generic data modality and formally prove its security. We then apply the generic construction to authenticating specific multimedia formats, for example, JPEG2000 code-streams and MPEG-4 video streams. The prototype implementation shows that our scheme is suitable for practical applications.